Investigation on the causes and method in minimizing the building defects - Azri Nurfathiah, Mustafa (2019)
Construction defects is a design flaw that occur on building that reduce the value of it and sometimes, may be hazard to life. The design flaw can be classified as any deficiency towards design building, workmanship, materials and sub-surface. It is common issue that associated with construction and can be happen either for an old or new building development. Numerous cases towards defects happen continuously in spite of the construction technology development nowadays. Hence, this research objectives are to investigate the type of defects work, study the causes factors that contribute to the defects works and analyze the method in minimizing the defects on building. The methodology of this study conducted by distributing the questionnaire to the party involved on site mainly site supervisor, contactor, developer and engineer estimating around 52 respondents. The structured questionnaire is divided into four elements which are foundation, structural, non-structural and roof to enhance the case study in searching the most causes factor contribute to each elements and methods which can minimize the associated defects. The data collection will be analyzed by using Relative Important Index (RII) method. The finding of this research, the causes factor that contribute to the defects are poor soil conditions, insufficient compaction for fresh concrete, poor workmanship that contribute to rough surface of plaster and water seepage and leakage underside of the roof. Moreover, the method to minimize the defects are using suitable concrete grade for foundation and structural elements., using proper paint and primer and having proper installation of roof tiles for pitched roof. Basically, any method applied on site can be as a guideline to minimize the occurrence of the defects from becoming more worst and to be concern, it must have good supervision and maintenance from the technical supervisor as well. Thus, this practice may help for construction industry to have an improvement towards defects and minimize the occurrence of it which can satisfy the customer.